Digital death: the inheritance of digital information - A. E. Kanakova (Правоприменение)
The subject of the research is the right to inherit digital information.The purpose of the research is to substantiate the need to conduct legal regulation of the consequences of the death of a person in the context of inheritance of digital data.The research is based on the analysis of sources of Russian and foreign law, as well as practical materials of Russian and foreign law in the sphere of rights and freedoms. The methodological basis of the research was formed by general scientific methods of cognition (analysis, synthesis, modelling) and private-scientific methods of cognition (comparativelegal, formal-logical).Main results. There are some approaches to the correlation of rights and freedoms realized in real and virtual space. The first approach considers digital or virtual rights and freedoms as a new legal phenomenon that requires separate legal regulation. The second approach assesses digital or virtual rights and freedoms as a manifestation of the features of those rights and freedoms that already exist outside the digital world. Although the first approach is more popular, the second approach is more correct because digital rights and freedoms either add a new territory of rights and freedoms or affect the mechanism of realization, but do not create a fundamentally new legal phenomenon.Because the death of a person does not automatically have consequences for the digital space, it is necessary to create a legal mechanism for recognising digital death, which will allow an individual who died in reality to become so for the virtual space. For the realisation of these powers it is not necessary to create completely new legal categories, it is enough to take into account the peculiarities of the realisation of offline rights and freedoms in virtual space.Conclusions. It seems more correct to move away from the concept of separating offline and online rights and to focus on the point-by-point introduction of digital rights and freedoms into existing legislation. Such an approach will not only ensure faster regulation of digital rights and freedoms, but will also make it possible to base legal regulation on provisions that have already had experience of implementation, and therefore identify possible gaps, problems, etc.